Exploring formalized elite coach mentoring programmes in the UK: `We`ve had to play the game` - Sawiuk, R.; Taylor, W. G.; Groom, R. (Sport, Education and Society, 2018)
Formalized mentoring programmes have been implemented increasingly by UK sporting institutions as a central coach development tool, yet claims supporting formal mentoring as an effective learning strategy are often speculative, scarce, ill-defined and accepted without verification. The aim of this study, therefore, was to explore some of the realities of formalized elite sports coaching mentoring programmes. Data were collected using semi-structured interviews with 15 mentors of elite coaches on formal programmes, across a range of sports. The findings were read through a Bourdieusian lens and revealed the importance of understanding the complexities of elite sports coaching environments, that elite sports coach development is highly specific and, therefore, should not be over-formalized, and how current elite sport coach mentoring programmes may be better conceptualized as a form of social control rather than being driven by pedagogical concerns. Following this empirically based analysis of practice, a number of implications for Governing Bodies, mentors and mentees were considered.